Genomic association and transcriptomic studies of bud break and fire blight resistance in apple germplasm for the development of cultivars better adapted to climate change : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Horticulture Science at Massey University, Palmerston North, New Zealand. EMBARGOED to 14 January 2027. - Chen, Xiaoying (Massey University, 2025)
This thesis investigates the genetic and phenotypic mechanisms underlying dormancy regulation and fire blight resistance in apples, with a focus on addressing the challenges posed by climate change. Employing a comprehensive approach that integrates genome-wide association studies (GWAS), RNA sequencing (RNA-seq) analysis, and advanced phenotyping techniques, this research aims to provide insights that support the development of climate-resilient apple cultivars. The study identifies significant genetic loci and candidate genes involved in endodormancy and ecodormancy transitions. Key genes such as MdDAM1, MdDAM2 and MdDAM4 reaffirm their established roles in dormancy regulation, while novel candidates, including CYP716A15, WRKY48 and XTH2, emerge as critical regulators during the progression from deep endodormancy to dormancy release. Similarly, genes like PP2C6, HSFC1 and CIPK1 are highlighted for their roles in the transition from dormancy maintenance to release, contributing to the understanding of genetic control during these phases. For fire blight resistance, phenotypic evaluations reveal variability in susceptibility among accessions, with M. baccata gracilis and Aotea 39 showing promise as novel sources of resistance. GWAS identified loci associated with polygenic resistance mechanisms, and RNA-seq provided evidence for the involvement of key resistance genes, including WRKY transcription factors and SIS proteins, in pathogen defence. This research also highlights methodological advancements and limitations. The use of single-node cutting (SNC) proved effective in differentiating dormancy phases, but challenges remain in achieving consistent phenotyping across diverse genetic backgrounds. The study underscores the need for enhanced sampling strategies, such as longitudinal RNA-seq, and the incorporation of advanced diagnostic tools, like hyperspectral imaging, to improve precision in trait assessments. The findings from this thesis offer a foundation for future breeding programs aimed at developing apple cultivars with reduced chilling requirements and enhanced resistance to fire blight. By addressing critical genetic and phenotypic gaps, this research contributes to the resilience and sustainability of apple production in the face of climate change.
Embargoed to 14 January 2027
Keywords: Apples; Disease and pest resistance; Climatic factors; New Zealand; Enzymes; Regulation; Fire-blight; 300804 Horticultural crop protection (incl. pests, diseases and weeds)